2002
DOI: 10.1007/s00464-001-8316-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy and common bile duct exploration are safe for older patients

Abstract: Elective laparoscopic CBD exploration is safe and effective. It may become the standard of care in both elderly and younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
(34 reference statements)
6
18
1
Order By: Relevance
“…The other study on LCBDE in the elderly has a reported mortality rate of only 1.3%. 28 This further supports our view that LCBDE can be safely performed in the elderly.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The other study on LCBDE in the elderly has a reported mortality rate of only 1.3%. 28 This further supports our view that LCBDE can be safely performed in the elderly.…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge, apart from this article, there is only one other study in the English literature looking specifically at LCBDE in the elderly. 28 In our study, there were 55 patients in the open group and 27 patients in the LCBDE group. All patients were over 70 years of age, and most were in ASA class II or III.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although the outcome of one specific laparoscopic procedure in general surgery has been evaluated for different age groups [18,19], there is no such study in laparoscopic urology. The present study is an initial report comparing two different age groups for LRN.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the mortality rate of surgery for stones in the common bile duct was 1.6–6.2% or even higher [7, 8, 9, 12]. Therefore, endoscopic treatment of common bile duct stones is the treatment of choice.…”
Section: Introductionmentioning
confidence: 99%